Self-assessment of a Master’s Degree Program at Educational Pedaghogy University: indicators for the quality accreditation - Graciela González Juárez (2020)
The objective of this work was to carry out a comparative analysis of the results of the self-evaluation of a master’s program of the National Pedagogical University in Mexico City (UPN) to attend three calls of the National Council of Science and Technology (Conacyt). The program has a presence of more than 15 years in external quality evaluations and has met the criteria and indicators established in the reference framework of the National Quality Postgraduate Program (PNPC) in Mexico. The methodology consisted of a comparative analysis of the information presented by the program regarding the study plan, the teaching staff and the students in terms of admission and graduation, in addition to the opinion of the graduates. The results show changes in the admission and graduation of students, in the assessment of competencies and in the terminal efficiency of the program. Self-evaluation is a necessary exercise to reflect on the quality of postgraduate programs and to establish improvement strategies that can be carried out by the actors, in a context where accreditation represents a challenge for educational programs offered educational institutions.